2019
DOI: 10.1257/aeri.20180063
|View full text |Cite
|
Sign up to set email alerts
|

The Violent Consequences of Trade-Induced Worker Displacement in Mexico

Abstract: Mexican manufacturing job loss induced by competition with China increases cocaine trafficking and violence, particularly in municipalities with transnational criminal organizations. When it becomes more lucrative to traffic drugs because changes in local labor markets lower the opportunity cost of criminal employment, criminal organizations plausibly fight to gain control. The evidence supports a Becker-style model in which the elasticity between legitimate and criminal employment is particularly high where c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 12 publications
1
47
0
Order By: Relevance
“…However, none of these papers attempt to identify the channels through which the trade-induced local shocks affect crime and none detect significant effects on violent crime (they study countries with relatively low crime levels-India and the United States-when compared to Brazil or most of Latin America and the Caribbean). 6 Finally, the paper contributes to the literature on the effects of labor market conditions on crime (Raphael and Winter-Ebmer 2001;Gould, Weinberg, and Mustard 2002;Lin 2008;Fougere, Kramarz, and Pouget 2009). In contrast to the Bartik shocks typically used as local labor demand shifters in this literature, we know precisely the source of the shock (changes in import tariffs), providing a more transparent source of exogenous variation.…”
mentioning
confidence: 90%
“…However, none of these papers attempt to identify the channels through which the trade-induced local shocks affect crime and none detect significant effects on violent crime (they study countries with relatively low crime levels-India and the United States-when compared to Brazil or most of Latin America and the Caribbean). 6 Finally, the paper contributes to the literature on the effects of labor market conditions on crime (Raphael and Winter-Ebmer 2001;Gould, Weinberg, and Mustard 2002;Lin 2008;Fougere, Kramarz, and Pouget 2009). In contrast to the Bartik shocks typically used as local labor demand shifters in this literature, we know precisely the source of the shock (changes in import tariffs), providing a more transparent source of exogenous variation.…”
mentioning
confidence: 90%
“…Recent research demonstrates that trade-induced job loss increases violence. For example, Dell, Feigenberg, and Teshima (2019) showed that Mexican manufacturing job loss induced by competition with China increases cocaine trafficking. For Indonesia, Kis-Katos and Sparrow (2011) showed that increased exposure to trade liberalisation is associated with a decrease in child work.…”
Section: Steps To Consider and Scope For New Issues And Methodsmentioning
confidence: 99%
“…Lastly, the seminal work by Becker (1968) predicts that the participation in illegal activities depends on the accessibility to legal economic opportunities. Dell et al (2019) find that a decline in manufacturing job opportunities caused by global trade with China increases drug-related violence.…”
Section: After Yeos Before Yeosmentioning
confidence: 96%